Multi-Physics Modeling of Steel Ingot Melting by Electric Arc Plasma and its Application to Electric Arc Furnace - Chen, Yuchao; Luo, Qingxuan; Silaen, Armin K.; Zhou, Chenn Q. (Frontiers in Materials, 2020)
Arc melting is one of the commonly-used melting methods in modern material manufacturing. The present study established a numerical model coupling the electric arc plasma, solid melting, and liquid flow together to simulate the steel ingot melting process using the electric arc. The direct current (DC) electric arc behavioral characteristics with varying arc length generated by the moving electrode were analyzed based on the validated model. The effects of both the initial arc length and the dynamic electrode movement on the steel ingot melting efficiency were studied. A potential method was also proposed to apply the established model in simulating the electric arc furnace (EAF) scrap melting. The study reveals that a reasonable and stable arc length can provide higher instantaneous heat flux and current density and reduce the arc dissipation, meanwhile balance the electrode consumption rate and melting efficiency to achieve the highest economic benefit. In addition, the dynamic electrode movement during the melting process maintains the original arc performance near the ingot top surface, which also results in a positive impact on the melting efficiency.